In Vivo Estrogen Regulation of Epidermal Growth Factor Receptor in Human Endometrium - McBean, Judith H.; Brumsted, John R.; Stirewalt, William S. (The journal of clinical endocrinology and metabolism, 1997)
The effects of estrogen and progesterone on the expression of epidermal growth factor receptor (EGFR) in human endometrium were studied in hypogonadal women under conditions that simulated a normal menstrual cycle. All women received the same regimen of estrogen and progesterone and underwent serial biopsies. In one group of women (group I), a biopsy was obtained before receiving estrogen (CD0) and after 11 days (CD11) of estrogen replacement. A second group of women was biopsied on CD11 and CD21 to assess the combined effects of progesterone and estrogen (group II). Immunohistochemistry was used to test for the presence of EGFR, and a ribonuclease protection assay was used to assess the amounts of EGFR messenger ribonucleic acid (RNA) relative to ribosomal RNA in the tissue. In group I, a significant increase in EGFR messenger RNA from CD0 to CD11 was observed. A similar increase was observed to occur between CD11 and CD21 in group II. Immunostaining for EGFR was absent in all CD0 biopsies, but was present in all estrogen-exposed endometrium. No difference in immunostaining was noted between CD11 and CD21. We conclude that estrogen stimulates the synthesis of EGFR in human endometrium and that progesterone does not appear to modulate this effect. The examination of other parameters in hormone-replaced hypogonadal subjects will be valuable in understanding the complex physiological regulation of the human endometrium.